2022
DOI: 10.1155/2022/9102565
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Viral Hepatitis B, C, and D in Kazakhstan

Abstract: Background. Viral hepatitis is a major burden for the healthcare system worldwide. Up to date, a comprehensive analysis of the prevalence of viral hepatitis in Kazakhstan and Central Asia has not been carried out yet. Our epidemiological study aimed at investigating the frequency and spread of viral hepatitis B, C, and D depending on age and sex in Kazakhstan (5-year period). Materials and Methods. We utilized the data from the primary registration of the incidence of hepatitis B, C, and D in 18 regions of Kaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…However, the global etiology of liver cirrhosis has changed, moving away from viral hepatitis owing to the availability of effective antiviral medications and shifts in lifestyle and dietary approaches. In Kazakhstan, the burden of viral hepatitis is substantial and continues to grow, as indicated by our findings and earlier scientific data 23 . Direct-acting antiviral hepatitis C drugs have not gained widespread use in Kazakhstan, and despite antiviral hepatitis B vaccination being included in the national vaccination schedule in 1998, the prevalence of anti‐HBcore antibodies was reported to be 17.2%, surpassing rates in many other countries 24 .…”
Section: Discussionsupporting
confidence: 71%
“…However, the global etiology of liver cirrhosis has changed, moving away from viral hepatitis owing to the availability of effective antiviral medications and shifts in lifestyle and dietary approaches. In Kazakhstan, the burden of viral hepatitis is substantial and continues to grow, as indicated by our findings and earlier scientific data 23 . Direct-acting antiviral hepatitis C drugs have not gained widespread use in Kazakhstan, and despite antiviral hepatitis B vaccination being included in the national vaccination schedule in 1998, the prevalence of anti‐HBcore antibodies was reported to be 17.2%, surpassing rates in many other countries 24 .…”
Section: Discussionsupporting
confidence: 71%
“…Kazakhstan is ranked as one of the countries with medium endemicity (2-7%) [17]. In 2020 about 23000 HBV cases were registered, the peak incidence was defined in West Kazakhstan, Kyzylorda region and Nur-Sultan city [18]. Approximately 21000 patients have CHB.…”
Section: Introductionmentioning
confidence: 99%
“…The recent study conducted by Jumabayeva et al in 2022 revealed a notable increase in new cases of hepatitis B, C, and D in Kazakhstan during the period of 2015-2020 [37]. This rise in hepatitis prevalence might heighten the necessity for an extensive approach to referring patients for liver cancer (LC) screening, as proposed by Harris et al in 2019 [38].…”
Section: Discussionmentioning
confidence: 99%